Surviving Japan – An Insider’s View of the Land of Bushido - Marko Lukić ([sic])
NOTE: Due to a possible editorial conflict of interest the author did not participate in the editing/publishing process of this issue of the journal.When considering the complexity and intricacy of Japanese history, as well as the endless innovation and colorfulness which defined, over the centuries, the development of martial arts in Japan, a potential reader might be a bit skeptical about the ability to pick up just one book and find a clear, well-structured, and informative overview of a large portion of Japanese history. However, Alexander Bennett in his book titled Japan: The Ultimate Samurai Guide manages to do just that. Starting with a somewhat obvious and unavoidable chapter on the actual and metaphoric meaning/value of the samurai, Bennett initiates a narrative journey that, through its approximately 150 pages, never falters in conveying the main issues and pinpointing various crucial historical turning points. By opening with a self-explanatory title to the first chapter – “Who were the Samurai?” – Bennett colloquially dives into the historical intricacies of the Japanese bushi (samurai), initially defined by their elite warrior status, only to become the ruling class of Japan in the period from the 12th to the 19th century. While relying on various illustrations, directly or indirectly related to the subject at hand (a narrative dynamic present through the entire text), the author manages not only to provide a succinct overview of some of the major samurai-era figures and occurrences, but he also enriches the discourse with numerous historical trivia facts, successfully avoiding in such a way the dangers of an overly static historical recount. Perhaps the most interesting segment within this samurai/male-based narrative is the one focusing on the outcasts – women warriors, the ronins (samurais without a “master”), and the popularized and (unnecessarily) mystified ninjas. It is within this segment that the author’s academic and real-life experience comes to life and becomes articulated through a series of verbal sketches which properly contextualize the various mythical and cultural approaches to Japanese history. This analytic tone continues in the following two chapters as well. The strongly titled chapters “Core Concepts of Bushido” and “Killing as an Art Form” necessitate a lighter narrative tone not only due to the attempt to simplify complex philosophical and existential paradigms, but also to more successfully expose the intricate cultural undertones which characterize Japanese martial traditions. Ranging from the highly-ritualized seppuku (ritual suicide) to politics, literature and, finally, to martial arts schools and the aesthetic of death, Bennett touches upon a number of critical moments and concepts, and by doing so, he traces an evolutionary path of the samurai thought all the way up to its modern incarnations. The fourth chapter, “Martial Arts in Japan Today,” summarizes the previously described traditions, folklore, and philosophies into Budo – the martial ways of Japan. Developed around the idea of self-cultivation through discipline and dedicated training, Budo becomes, through the narrative of the author, not only a path to self-perfection but also an educational tool, as well as an active narrative, developed and modernized with the aim of internationally promoting Japan. Although this chapter could mark a logical conclusion to the narrative arc of the book, Bennett opts for two additional chapters titled “Life in a Japanese Dojo” and “Surviving Japan.” It is with these two chapters that the title of the book itself becomes much clearer. Instead of a potentially structurally rigid (although humorous) history lesson, the author reaches for years of his own personal experience in living, training, and working in Japan. The result is a fascinating, although unfortunately brief rundown of rules, traditions, and customs to which a non-Japanese ind